PI3K/AKT/mTOR Pathway in Angiogenesis - Karar, Jayashree; Maity, Amit (Frontiers in Molecular Neuroscience, 2011)
The phosphatidylinositol 3-kinase (PI3K)/AKT/mTOR pathway is activated in the majority of human cancers. This pathway is known to play a key role in numerous cellular functions including proliferation, adhesion, migration, invasion, metabolism, and survival, but in the current review we focus on its role in angiogenesis. PI3K activation may occur via RAS mutation, loss of PTEN, or by increased expression of growth factor receptors such as EGFR. There is a connection between the PI3K pathway and angiogenesis. Hypoxia leads to HIF-1α stabilization and is a major stimulus for increased VEGF production by tumor cells. However, activation of the PI3K/AKT pathway in tumor cells can also increase VEGF secretion, both by HIF-1 dependent and independent mechanisms. The PI3K/AKT pathway also modulates the expression of other angiogenic factors such as nitric oxide and angiopoietins. Numerous inhibitors targeting the PI3K/AKT/mTOR pathway have been developed, and these agents have been shown to decrease VEGF secretion and angiogenesis. The effect of these inhibitors on tumor vasculature can be difficult to predict. The vasculature of tumors is aberrant, leading to sluggish bloodflow and elevated interstitial blood pressure, which can be perpetuated by the high levels of VEGF. Hence, decreasing VEGF expression can paradoxically lead to vascular normalization and improved bloodflow in some tumors. In addition to its importance in cancer, the PI3K pathway also plays an essential role in the formation of normal blood vessels during development. Embryos with kinase-dead p110α catalytic subunit of PI3K develop vascular defects. Simulation of endothelial cells by VEGF leads to activation of the PI3K pathway within these cells, which is important for cell migration. Sustained endothelia1 activation of AKTl has been shown to induce the formation of structurally abnormal blood vessels that recapitulate the aberrations of tumor vessels. Hence, the PI3K pathway plays an important role